Radiographic Evaluation During Treatment of Pediatric Forearm Fractures: Implications on Clinical Care and Cost. Issue 5 (July 2016) - Luther, Gaurav; Miller, Patricia; Waters, Peter M.; Bae, Donald S.
Abstract : Background: As ≥30% of displaced pediatric forearm fractures demonstrate loss of reduction (LOR) following closed reduction (CR); radiographic follow-up is advocated at 1, 2, 4, and 6 weeks for detection of redisplacement. We hypothesized that there is minimal change in fracture alignment 2 weeks after CR, and consequently, that radiographs at 4 weeks add cost but little value to clinical care. Methods: A total of 184 patients enrolled in a prospective study of pediatric forearm fractures including both distal and diaphyseal injuries were evaluated. All were treated with CR, casting, and radiographic evaluation at 1, 2, 4, and 6 weeks postinjury. Primary endpoint was radiographic LOR. Secondary endpoint was need for any intervention. A modified number-needed to treat analysis estimated the utility of the week 4 x-ray in predicting intervention. Relative value unit (RVU) costing, time-derived activity-based costing (TDABC), and billing totals were used for cost analysis. Results: Seventy patients (38%) demonstrated radiographic LOR. Independent predictors of LOR were initial radius displacement >75% (OR=5.40; CI, 2.23-12.60), concomitant ulna fracture (OR=1.71; CI, 1.15-2.54), and dominant arm involvement (OR=2.87; CI, 1.40-5.87). Eighty percent of all LORs occurred within the first 2 weeks. There was no statistically significant change in radiographic alignment after week 2. Of 40 total interventions, all were performed within the first 2 weeks of follow-up. The 4-week x-ray did not influence decision to intervene, and at most, 1 in every 40 patients would require an intervention after week 2. Elimination of the 4-week x-ray would result in a savings of 4.8% (RVU method) to 11.9% (TDABC method) in the overall cost of nonoperative fracture care. Conclusions: There is minimal change in fracture alignment 2 weeks following CR of pediatric forearm fractures, and all interventions are based on early radiographic follow-up. The week 4 x-ray adds little value to clinical decision making, and its elimination would result in savings up to 11.9% of the overall cost of nonoperative fracture care. Level of Evidence: Level II—prognostic.